2014
DOI: 10.1007/s11684-014-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal dilatation of the aortic sinuses of Valsalva — beyond Marfan syndrome: a single centre experience and review of the literature

Abstract: Aneurysmal dilatation of the aortic sinuses of Valsalva has been most extensively documented in the setting of aortopathies, particularly Marfan syndrome. On the other hand, there is limited data in the literature about congenital sinus of Valsalva aneurysms outside this context. For the purpose of this review, we carried out a literature search on aneurysmal dilatation of the sinuses of Valsalva in Marfan syndrome, and compared this with congenital sinus of Valsalva aneurysms, also including data from a case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, the rate of incidence is highly dependent on the population under analysis. It is noted that men are more often affected than women and Asian descent is a risk factor (6,7). It has been shown that the right sinus of Valsalva (RSoV) is affected most often.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rate of incidence is highly dependent on the population under analysis. It is noted that men are more often affected than women and Asian descent is a risk factor (6,7). It has been shown that the right sinus of Valsalva (RSoV) is affected most often.…”
Section: Discussionmentioning
confidence: 99%
“…SoV aneu-rysms are often attributed to congenital pathologies. Congenital diseases that can lead to SoV aneurysm are Marfan syndrome, Ehlers-Danlos syndrome, Loeys-Dietz syndrome, and other rare connective tissue disorders (5,6). On the other hand, different acquired pathologies can also weaken the aortic wall and lead to dilation.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions consist of outpouchings through the aortic root between the aortic valve annulus and the sinotubular ridge. There is a higher incidence in males and in certain Asian populations .…”
Section: Discussionmentioning
confidence: 99%
“…5,9 Sinus of Valsalva aneurysms have also been described in patients with Klippel-Feil syndrome, cutis laxa, and Treacher-Collins syndrome. 10 While the cornerstones for establishing a diagnosis continue to be a complete medical history, a detailed three-generation family history, and a comprehensive physical examination, there is great phenotypic overlap among CTDs. 11 Clinicians often proceed with ordering molecular or cytogenetic studies in an attempt to reach a definitive diagnosis in hopes it will allow for improved counseling and will guide clinical monitoring and intervention.…”
Section: Introductionmentioning
confidence: 99%